Gambaran Perilaku Hidup Bersih dan Sehat Warga Lingkungan 6 Kelurahan Mahawu Kecamatan Tuminting Kota Manado - Kandou, Grace D.; Lampus, Benny S.; Wijaya, Nur Estriana Anugrahwaty (UNIVERSITAS SAM RATULANGI, 2013)
Clean and Health Behaviour is one of the health promotion program’s priorities made by the government through clinic and become a target of the health management. Tuminting includes of nine sub districts in Manado City. Because no reports are discovered about the description of Clean and Health Behavior on Residents in Region 6 Tuminting Sub-District, the writer is interested to research about this issue. This research is aimed to discover the description of CnHB of Residents on Residents in Region 6 Mahawu District, Tuminting Sub-District including: Medical Team’s involve on childbirth, exclusive breastfeeding, availability of clean water, usage of clean water and soap on hand washing, availability of health latrine, larvae’s eradication in houses, fruits and vegetables’ daily consume, daily physical activity and not smoking inside the house. This research is a descriptive research with 81 respondents. The data are collected by interview based on questionnaire and presented by using tabulation and percentage. The research shows a great result of CnHB on Residents in Region 6 Mahawu District, Tuminting Sub-District. Around 67% represents good knowledge and 33% for bad knowledge, 75% represents good attitude and 25% for bad attitude, 54% represents good behavior and 46% for bad behavior.Keywords: socioeconomic status, nutritional status. Keywords: Clean and Health Behaviour, Knowledge, Attitude and Behaviour